2004
DOI: 10.1007/s00531-004-0409-4
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy and paleomagnetism of a 2.9-km composite lava section in Eyjafj�rdur, Northern Iceland: a reconnaissance study

Abstract: Eight mountainside profiles in lava flows south of the fjord Eyjafjördur, Northern Iceland, were sampled for paleomagnetic studies. The sampling was concurrent with pilot stratigraphic mapping of the lava sequences in these and several supplementary profiles. The eight profiles are correlated with minor overlaps so that they form a composite section of 2.9 km thickness, estimated to cover the age range between about 9 and 5 million years ago (Hardarson et al. 1999). Paleomagnetic measurements made on 319 lavas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…However, later research has indicated that the volcanic productivity is quite episodic, and dating of a thick normal-polarity zone in Northwestern Iceland (McDougall et al, 1984) did not yield the expected agreement with the two thick zones dated previously. In some cases the paleomagnetic directions in successive lavas are serially correlated, indicating that the time interval between these lavas is less than 1 kyear (Kristjansson et al, , 2004. In other cases there may be hiatuses of 100 kyear and more between lava flows, not detectable from geologic observations or from radiometric dating at the present level of resolution.…”
Section: Some Further Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…However, later research has indicated that the volcanic productivity is quite episodic, and dating of a thick normal-polarity zone in Northwestern Iceland (McDougall et al, 1984) did not yield the expected agreement with the two thick zones dated previously. In some cases the paleomagnetic directions in successive lavas are serially correlated, indicating that the time interval between these lavas is less than 1 kyear (Kristjansson et al, , 2004. In other cases there may be hiatuses of 100 kyear and more between lava flows, not detectable from geologic observations or from radiometric dating at the present level of resolution.…”
Section: Some Further Resultsmentioning
confidence: 84%
“…Other examples are found in papers by Sigurgeirsson (1957), Kristjansson (1995) and Kristjansson et al (2004). Field mapping of remanence directions in late-glacial lavas of the Reykjanes peninsula, initiated by A. Gudmundsson in the mid-1970s, revealed that in several hills all exposed lava flows were erupted during a geomagnetic transition or major excursion of the field (Levi et al, 1990).…”
Section: Some Further Resultsmentioning
confidence: 95%
See 3 more Smart Citations